Biscuit's new trick - Capucilli, Alyssa Satin, 1957-; Schories, Pat (New York : HarperCollins, 2000)
A puppy does all sorts of tricks in the process of learning the one his master is trying to teach him.
Keywords: Biscuit (Fictitious character) -- Juvenile fiction; Puppies -- Training -- Juvenile fiction; Biscuit (Fictitious character) -- Fiction; Dogs -- Training -- Fiction